Pelatihan Materi Teknologi Augmented Reality Untuk Meningkatkan Keterampilan Siswa di SMK TI Pembangunan Kota Cimahi - Tati Ernawati; Iqbal Heriyadi; Muhammad Apipudin Safaat; Sela Pebriana (PUAN INDONESIA, 2024)
As technological developments continue to evolve, the opportunity to integrate augmented reality into the educational curriculum makes learning more enjoyable. Observation results reveal that SMK IT Development students have never received Augmented Reality technology material, despite their high enthusiasm for it. Regarding the issue, the team proposed providing Augmented Reality material to students in training. The purpose of the training is to inform the participants about Augmented Reality. The course of PkM activities consists of four main activities: preparation, observation, implementation of activities, and reporting. The results of the training activities showed the participants very good responses and enthusiasm shown by their activity during the course of the activity. With the positive response from the excellent school, the school hopes this activity will be held continuously and carried out for more than one day. Augmented Reality material is a new material learned by the participants, so attract their curiosity to learn it. The evaluation results for further improvements in training activities are training materials developed for broader language topics with longer durations, such as Augmented Reality implementation materials on mobile device platforms